The Influence Of E-Service Quality And E-Trust On Lazada E-Loyalty (Survey On Lazada Customers In Tasikmalaya City): - Nurhasanah, Siti; Askolani (Jurnal Ekonomi, Manajemen, Bisnis dan Akuntansi, 2024)
This study aims to determine the effect of e-service quality and e-trust on Lazada e-loyalty. The method used is a quantitative method with a research sample of 100 respondents. The data used are primary and secondary data. The analytical tool used in this research is multiple linear regression analysis using SPSS version 25. Based on the results of this study, it shows that e-service quality and e-trust simultaneously have a positive and significant effect on e-loyalty. e-service quality partially has a significant effect on e-loyalty and e-trust partially has a significant effect on e-loyalty.